Paradoxes and Challenges for China's Forests in the Reform Era*. (7th April 2014) - Robbins, Alicia S.T.; Harrell, Stevan
Abstract: China's relatively recent dramatic increase in forest area has been hailed domestically and globally as one of the world's few environmental success stories, but significant problems remain in China's reforestation efforts. We describe the challenges that China still faces if it is to meet its laudable – but sometimes contradictory – goals for its forest sector: improving rural livelihoods, sustaining and restoring ecosystem services, and increasing output of the forest product-dependent manufacturing and construction sectors. We do so while pointing out the unintended consequences of implementing these policy goals: overstatement of the quantity and quality of the forest recovery, domestic human and ecological costs of the reforestation, and externalization of China's continually growing demand for timber and forest products in the form of increased imports from vulnerable forests in other parts of the world.